The Acute Effects of Normobaric Hypoxia on Strength, Muscular Endurance and Cognitive Function: Influence of Dose and Sex - Karayiğit, Raci; Eser, Mustafa Can; Şahin, Fatma Neşe; Sarı, Cengizhan; Sanchez-Gömez, Angela; Dominguez, Raul; Koz, Mitat (Mdpi, 2022)
Simple Summary Hypoxic training is a novel method to increase resistance training adaptations. There is some evidence that resistance exercise performed in systemic hypoxia can lead to structural and functional adaptations of skeletal muscle. Studies have also demonstrated that normobaric hypoxia (i.e., normal pressure, low oxygen) increases intramuscular metabolic stress and type two (fast twitch) fiber recruitment, which leads to a greater morphological adaptations over time. However, to date, there is no research that has investigated the effects of different doses of acute normobaric hypoxia on strength and muscular endurance performance, nor has there been research investigating potential sex-based differences. The aim of this study was to examine the acute effects of different levels of hypoxia on maximal strength, muscular endurance, and cognitive function in males and females. In total, 13 males (mean +/- SD: age, 23.6 +/- 2.8 years; height, 176.6 +/- 3.9 cm; body mass, 76.6 +/- 2.1 kg) and 13 females (mean +/- SD: age, 22.8 +/- 1.4 years; height, 166.4 +/- 1.9 cm; body mass, 61.6 +/- 3.4 kg) volunteered for a randomized, double-blind, crossover study. Participants completed a one repetition strength and muscular endurance test (60% of one repetition maximum to failure) for squat and bench press following four conditions; (i) normoxia (900 m altitude; FiO2: 21%); (ii) low dose hypoxia (2000 m altitude; FiO2: 16%); (iii) moderate dose hypoxia (3000 m altitude; FiO2: 14%); and (iv) high dose hypoxia (4000 m altitude; FiO2: 12%). Heart rate, blood lactate, rating of perceived exertion, and cognitive function was also determined during each condition. The one repetition maximum squat (p = 0.33) and bench press (p = 0.68) did not differ between conditions or sexes. Furthermore, squat endurance did not differ between conditions (p = 0.34). There was a significant decrease in bench press endurance following moderate (p = 0.02; p = 0.04) and high (p = 0.01; p = 0.01) doses of hypoxia in both males and females compared to normoxia and low dose hypoxia, respectively. Cognitive function, ratings of perceived exertion, and lactate were also significantly different in high and moderate dose hypoxia conditions compared to normoxia (p < 0.05). Heart rate was not different between the conditions (p = 0.30). In conclusion, high and moderate doses of acute normobaric hypoxia decrease upper body muscular endurance and cognitive performance regardless of sex; however, lower body muscular endurance and maximal strength are not altered.
Keywords: hypoxic dose; resistance training; muscular endurance; sex difference; flanker; Blood-Flow Restriction; Performance Responses; Exercise Performance; Muscle Hypertrophy; Resistance; Recovery; Fatigue; Gender; Women